Efforts to Improve the Ability to Understand Trogonometry Concepts by Implementing the Discovery Learning Model of Students in Class XI SMA IT Persis Palu - Sahabudin, Nurfadila; Hadjar, Ibnu; Pathuddin; Fajriani (Desimal, 2026)
The growing demand for twenty-first century competencies has increased the need for mathematics instruction that promotes conceptual understanding, reflective reasoning, and active student engagement. However, trigonometry learning in many secondary schools remains dominated by procedural instruction and formula memorization, causing students to experience difficulties in understanding conceptual relationships. This study aimed to investigate the implementation of the discovery learning model in improving students’ conceptual understanding of trigonometry among class XI students at SMA IT Persis Palu, Indonesia. The study employed a qualitative-dominant Classroom Action Research design conducted through two iterative cycles consisting of planning, action, observation, and reflection stages. The participants involved 23 students, with three focal informants selected purposively based on preliminary conceptual difficulties. Data were collected through conceptual understanding tests, classroom observations, interviews, field notes, and documentation. The findings revealed substantial improvement in students’ conceptual understanding across all indicators, including the ability to restate concepts, identify conceptual relationships, distinguish examples and non-examples, and apply trigonometric concepts accurately in contextual problem-solving situations. Learning mastery increased progressively until 88.24% of students achieved the minimum competency criterion in Cycle II. The study concludes that discovery learning effectively facilitates conceptual reconstruction, collaborative inquiry, and meaningful mathematical understanding in secondary trigonometry learning.